2016
DOI: 10.1111/jeu.12343
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Trypanosome Peroxin to the Endoplasmic Reticulum

Abstract: Trypanosoma brucei is the causative agent of diseases that affect 30,000–50,000 people annually. Trypanosoma brucei harbors unique organelles named glycosomes that are essential to parasite survival, which requires growth under fluctuating environmental conditions. The mechanisms that govern the biogenesis of these organelles are poorly understood. Glycosomes are evolutionarily related to peroxisomes, which can proliferate de novo from the endoplasmic reticulum or through the growth and division of existing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…This strengthens our theory that matrix proteins are more likely to require a PTS1 or PTS2 to be properly localized than glycosome membrane proteins or complexes that may derive from the likely glycosome biogenesis involving the ER or even the mitochondrion [28,33]. In the case of PEX13.1, the protein is dual localized, and its PTS1, "TKL", is known to be important for its glucose-dependent glycosome localization [34]. We also analyzed the remaining~100 proteins to determine how many possessed domains indicating a role in pathways clearly unrelated to glycosome function.…”
Section: Utilizing the Pts1 Signal Algorithm In Other Datasetssupporting
confidence: 77%
“…This strengthens our theory that matrix proteins are more likely to require a PTS1 or PTS2 to be properly localized than glycosome membrane proteins or complexes that may derive from the likely glycosome biogenesis involving the ER or even the mitochondrion [28,33]. In the case of PEX13.1, the protein is dual localized, and its PTS1, "TKL", is known to be important for its glucose-dependent glycosome localization [34]. We also analyzed the remaining~100 proteins to determine how many possessed domains indicating a role in pathways clearly unrelated to glycosome function.…”
Section: Utilizing the Pts1 Signal Algorithm In Other Datasetssupporting
confidence: 77%
“…A global analysis of localized protein synthesis also revealed that many PMPs are likely cotranslated at the ER (Jan et al, 2014). Similar observations of PMP cotranslation (Kaewsapsak et al, 2017) and transport from ER to peroxisomes made in substantially divergent species of yeast (Agrawal et al, 2011; Farre et al, 2017; Titorenko and Rachubinski, 1998), plants (Hu et al, 2012), the excavate pathogen Trypanosoma brucei (Bauer et al, 2017; Guther et al, 2014), and mammalian cells (Kim et al, 2006; Mayerhofer et al, 2016) highlight the essential and evolutionarily ancient role of the ER in peroxisome biogenesis in eukaryotic cells.…”
Section: Introductionsupporting
confidence: 54%
“…Additionally, our lab found that TbPEX13.1 localized to the ER in PF T . brucei under low-glucose conditions [ 59 ]. Because peroxins localize to the ER in other organisms during de novo biogenesis, it is interesting to speculate that TbPEX13.1 localizes to foci in the ER where new glycosomes or preglycosomal vesicles bud.…”
Section: Recent Studies Suggest Glycosomes Can Proliferate De Novo Inmentioning
confidence: 99%
“…This may explain why glucose-dependent changes in glycosome composition occur in a time frame consistent with autophagy [ 68 ]. (B) “New” organelles with protein repertoires better suited to the new levels of glucose in the environment can be generated from the ER [ 48 , 49 , 59 , 60 , 68 70 ]. (C) Once new glycosomes are generated, they can be maintained through fission [ 26 ].…”
Section: Recent Studies Suggest Glycosomes Can Proliferate De Novo Inmentioning
confidence: 99%
See 1 more Smart Citation